A Monograph on Theoretical Understanding of the Contradictions of Vested Interests and Underdevelopment in Peripheral Social Formation - Ogbonna, Hyginus Obinna (Mediterranean Journal of Social Sciences, 2021)
This paper focuses on theoretical understanding of the contradictions of vested interests and the underdevelopment in the peripheral social formations; having as its raison d'être, to explore the possible ways by which the vested interests of a particular social group or class has contributed in shaping the underdevelopment of the periphery in the global economy –with inferences from a sub-Saharan African country, Nigeria (with empirical-based evidences); and moving forward, to find ways to counteract or mitigate these contradictions for the amelioration of the human condition in the periphery. Thus, the paper achieves its objectives by adopting a qualitative descriptive method of analysis, investigating the contradictions of the vested interests of both the neo-colonial elite in the Periphery and the capitalists of the Center (advanced capitalist nations), with an admixture of "Dependency Perspective" in its exploration. A theoretical framework, Marxian Ideology, was employed to help for a better epistemic understanding of the dynamics of vested interests aided by helpful extrapolations in its analysis. In the final analysis, the paper made some findings. A few of these include, 1) that the ruling class of the peripheral nations, especially in Africa (typically, Nigeria) has the culture of diverting national wealth for own personal interest. 2) That every moment of domination precipitates moments of resistance by the subjugated class, hence revolutions and instability are endemic in any polity fraught with vested interests of the dominant class. 3) That the peripheral nations have remained underdeveloped due to the selfish interests of both the peripheral ruling class (the puppets of the capitalist of the Center) and the advanced capitalist nations. The paper therefore recommends: that the peripheral social formations should pursue serious independent policies of social justice along egalitarian lines as well as economic and political self-reliance –e.g. state incentives for local industrialists and integrating and strengthening the domestic productive base to attain a self-reliant articulated economy. 2) There is need for total commitment to democratic ethos or permissiveness including popular-empowerment in every aspect for the amelioration of the human condition; among others.   Received: 29 May 2021 / Accepted: 30 June 2021 / Published: 8 July 2021